Direct ELISA aided coprological diagnosis of Cryptosporidium parvum infection in diarrheic neonatal calves in Mosul city, Iraq - Al-Robaiee, Israa; Al-Farwachi, Maab (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted for the detection of Cryptosporidium (C.) parvum infection in neonatal calves. A total of 220 fecal samples (diarrheic 110 and non-diarrheic 110) of neonatal calves were collected from Mosul city, Iraq over a period of 16 months from November 2010 to March 2012. The age of the calves ranged from 1 to 30 days. All the fecal samples were analyzed by capture direct ELISA. The infection was found in 29.0% (n=32/110) of the diarrheic calves. The infection was mostly prevalent (p<0.001) in the calves of three weeks of age. No C. parvum infection could be detected in the non-diarrheic animals. DOI: http://dx.doi.org/10.5455/javar.v1i1p8-10 J. Adv. Vet. Anim. Res., 1(1): 8-10, March 2014